Recreating H'Mong ethnic culture through the cinematic perspective: the case of the documentary 'Children of the Mist' = Penciptaan semula budaya etnik H'Mong melalui perspektif sinematik: kajian kes terhadap filem dokumentari Children of the Mist - Truong, Nguyen Khanh Dan; Nguyen, Vo Huong My; Lu, Hoang Phuong Thao; Tran, Khanh Van; Nguyen, Thi Thao Ly; Nguyen, Tan Khang (UUM PRESS, 2025)
This study examines how the documentary Children of the Mist (2021) represents the material and spiritual culture of the H’mong ethnic group. Material culture includes housing architecture, traditional clothing, and indigo dyeing techniques, while spiritual culture encompasses marriage customs, festivals, religious beliefs, and social practices. Employing content analysis and cross-referencing with ethnographic literature, the study applies Roland Barthes’ semiotic theory and Hans-Georg Gadamer’s hermeneutic approach to assess the authenticity and symbolic meaning of cultural representations in the film. Findings indicate that the film effectively portrays the distinctive cultural characteristics of the H’mong people, illustrating the tensions between tradition and modernity, particularly regarding child marriage and educational aspirations among younger generations. However, certain details in the film diverge from ethnographic records, such as modifications in marriage practices and ceremonial rituals. This study underscores the crucial role of documentary films in preserving and disseminating ethnic cultures, records of reality but as discursive mediums shaping national and ethnic identity in a globalized context. By depicting the material and spiritual culture of indigenous communities, documentaries can enhance public awareness of cultural heritage while serving as educational tools and platforms for cross-cultural dialogue. To optimize this role, the study advocates for close collaboration between filmmakers and ethnographic scholars to ensure accuracy and representational integrity in cinematic portrayals of ethnic cultures.